Generasi Z dan Teknologi : Gaya Hidup Generasi Z di Era Digital - Oktavia Ramadhani; Khoirunisa Khoirunisa (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
Generation Z has grown up in an era of rapid digital technological advancement, making them highly dependent on technology. This study aims to analyze how technology impacts the lifestyle of Generation Z in the digital era. Using a qualitative descriptive approach, data was collected through observation and literature review. The results indicate that Generation Z is characterized by being highly digital, independent, and prioritizing flexibility in both work and communication. The primary impact of technology on their lifestyle is how they communicate. Social media has become their main channel for interacting, sharing experiences, and shaping their social identity.